2016
DOI: 10.1007/s00033-016-0652-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale analysis of the acoustic scattering by many scatterers of impedance type

Abstract: We are concerned with the acoustic scattering problem, at a frequency κ, by many small obstacles of arbitrary shapes with impedance boundary condition. These scatterers are assumed to be included in a bounded domain Ω in R 3 which is embedded in an acoustic background characterized by an eventually locally varying index of refraction. The collection of the scatterers Dm, m = 1, ..., M is modeled by four parameters: their number M , their maximum radius a, their minimum distance d and the surface impedances λm,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…We call the upper bounds of the Lipschitz character of B m 's, M m a x , d m i n , d m a x , and κ m a x the set of the apriori bounds. In , we have shown that there exist a positive constant a 0 , λ − , and λ + depending only on the set of the apriori bounds and on n m a x such that if aa0,2.56804pt|λm,0|λ+,2.56804pt|R(λm,0)|λ,2.56804pt1em1emβ<1,2.56804pt1em1ems2β,2.56804pt1em1ems3t then the far‐field pattern U(truex̂,θ) has the following asymptotic expansion U(truex̂,θ)=Vn(truex̂,θ)+m=1MVnt(truex̂,zm)double-struckQm+O()a3s2β, uniformly in truex̂ and θ in double-struckS2. The constant appearing in the estimate O (.)…”
Section: Statement Of the Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We call the upper bounds of the Lipschitz character of B m 's, M m a x , d m i n , d m a x , and κ m a x the set of the apriori bounds. In , we have shown that there exist a positive constant a 0 , λ − , and λ + depending only on the set of the apriori bounds and on n m a x such that if aa0,2.56804pt|λm,0|λ+,2.56804pt|R(λm,0)|λ,2.56804pt1em1emβ<1,2.56804pt1em1ems2β,2.56804pt1em1ems3t then the far‐field pattern U(truex̂,θ) has the following asymptotic expansion U(truex̂,θ)=Vn(truex̂,θ)+m=1MVnt(truex̂,zm)double-struckQm+O()a3s2β, uniformly in truex̂ and θ in double-struckS2. The constant appearing in the estimate O (.)…”
Section: Statement Of the Resultsmentioning
confidence: 99%
“…Hence, the total field U t := U i + U s satisfies the following exterior impedance problem of the acoustic waves (normalΔ+κ2n2(x))Ut=0indouble-struckR3()m=1MtrueD̄m, |Utνm+λmUtDm=0,0.3em1mM, Us|x|Us=o()1|x|,|x|, Again, the scattering problem – is well‐posed in the Hölder or Sobolev spaces (see in the case I λ m >0). As we said for –, this last condition can be relaxed to allow I λ m to be negative . Applying Green's formula to U s , we can show that the scattered field U s ( x , θ ) has the following asymptotic expansion: Us(x,θ)=e|x|4π|x|U(truex̂,θ)+O(|x|2),1em|x|, where the function U(truex̂,θ) for (truex̂,θ)double-struckS2...…”
Section: Statement Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have two cases as follows: Under the conditions, on κ , that τ:=minijcosfalse(κfalse|zizjfalse|false)>0 and if C m ( κ 0 , λ m ) is positive with Lmfalse(κ0,λmfalse)d uniformly bounded, in terms of a , from above by a certain constant, then the above algebraic system is invertible and hence κ is not a quasi‐resonance (or even a resonance), see Challa and Sini …”
Section: Proof Of Theorem 14mentioning
confidence: 99%